Antibiotic prophylaxis for ophthalmia neonatorum in Italy: results from a national survey and the Italian intersociety new position statements - Vito Mondì; Chryssoula Tzialla; Salvatore Aversa; Daniele Merazzi; Stefano Martinelli; Gabriella Araimo; Luca Massenzi; Giacomo Cavallaro; Luigi Gagliardi; Fiammetta Piersigilli; Mario Giuffrè; Simona Lozzi; et al. (BMC, 2023)
Abstract Background Ophthalmia neonatorum is an acute conjunctivitis that occurs in newborns within the first month of life. The most serious infections are due to Chlamydia trachomatis and Neisseria gonorrhoeae, that may cause permanent damages. The use of ophthalmic prophylaxis varies widely around the world, according to the different health and socio-economic contexts. To date in Italy there is no a clear legislation regarding ophthalmia neonatorum prophylaxis at birth. Methods We invited all birth centers in Italy to carry out a retrospective survey relating the last three years. We collected data regarding demographics of neonates, drugs used for ophthalmic prophylaxis and results of the screening of pregnant women for Chlamydia trachomatis and Neisseria gonorrhoeae vaginal infections. Results Among 419 birth centers, 302 (72,1%) responded to the survey. Overall 1041384 neonates, 82,3% of those born in the three years considered, received ophthalmic prophylaxis. Only 4,585 (0,4%) of them received one of the drugs recommended by the WHO. The Centers that participated to the survey reported 12 episodes of Chlamydial conjunctivitis and no Gonococcal infection in the three years. Only 38% of the Centers performed vaginal swabs to pregnant women: 2,6% screened only for Neisseria, 9,6% only for Chlamydia and 25,8% for both germs. Conclusions The data obtained from the survey showed a low incidence of neonatal conjunctivitis due to either Neisseria gonorrhoeae or Chlamydia trachomatis in Italy. Due to the lack of legislation regulating the prophylaxis of ophthalmia neonatorum in newborns, the Italian Society of Neonatology, the Italian Society of Obstetrics and Gynecology and the Italian Society of Perinatal Medicine have recently issued new recommendations on this topic.